2011
DOI: 10.1111/j.1551-6709.2011.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflection and Reasoning in Moral Judgment

Abstract: While there is much evidence for the influence of automatic emotional responses on moral judgment, the roles of reflection and reasoning remain uncertain. In Experiment 1, we induced subjects to be more reflective by completing the Cognitive Reflection Test (CRT) prior to responding to moral dilemmas. This manipulation increased utilitarian responding, as individuals who reflected more on the CRT made more utilitarian judgments. A follow-up study suggested that trait reflectiveness is also associated with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
294
3
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(334 citation statements)
references
References 33 publications
20
294
3
17
Order By: Relevance
“…Our findings are consistent with previous work demonstrating that disfluency enhances analytic thinking, thus improving performance in cognitive tasks (Alter et al, 2007;Diemand-Yauman et al, 2010;Song & Schwarz, 2008). Increased analytic thinking can also promote utilitarian responses to moral dilemmas (Bartels, 2008;Moore et al, 2008;Paxton et al, 2012). In our study, dilemmas written in disfluent fonts may have prompted analytic thinking in participants, leading to more utilitarian decisions.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are consistent with previous work demonstrating that disfluency enhances analytic thinking, thus improving performance in cognitive tasks (Alter et al, 2007;Diemand-Yauman et al, 2010;Song & Schwarz, 2008). Increased analytic thinking can also promote utilitarian responses to moral dilemmas (Bartels, 2008;Moore et al, 2008;Paxton et al, 2012). In our study, dilemmas written in disfluent fonts may have prompted analytic thinking in participants, leading to more utilitarian decisions.…”
Section: Discussionsupporting
confidence: 82%
“…Stanovich (e.g., 2004;2009b) has argued that thinking disposition is an underappreciated determinant of psychological outcomes. Recent research has supported the idea that cognitive style plays a consequential role in psychological domains that are of some general import (Pennycook, Fugelsang, & Koehler, 2015b): e.g., creativity (Barr, Pennycook, Stolz, & Fugelsang, 2014), moral judgments and values (Paxton, Unger, & Greene, 2012;Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2014b;Rozyman, Landy, & Goodwin, 2014), religious belief (Gervais & Norenzayan, 2012;Pennycook et al, 2014a;Pennycook, Cheyne, Koehler, & Fugelsang, 2013;Pennycook, Ross, Koehler, & Fugelsang, 2016;Shenhav, Rand, & Greene, 2012), bullshit receptivity (Pennycook, Cheyne, Barr, Koehler, & Fugelsang, 2015), and even Smartphone technology use (Barr, Pennycook, Stolz, & Fugelsang, 2015 …”
Section: Individual Differences In Analytic Thinkingmentioning
confidence: 99%
“…Several studies have found that fictitious cases of consensual incest evoke strong disgust reactions, even when participants are given supplementary information suggesting that there was no chance of conception and that no emotional harm would come from the incestuous encounter (GinerSorolla & Russell, 2009;Haidt, Koller, & Dias, 1993;Paxton, Ungar, & Greene, 2011).…”
mentioning
confidence: 99%